Pelatihan Pembuatan Abon Ikan Untuk Meningkatka Pendapatan Masyarakat di Desa Secanggang, Kecamatan Secanggang - Irga Maulana; Iis Daniati Lubis; Diani Syahfitri (peduli riset dan pengabdian masyarakat, 2024)
Secanggang Village, Secanggang District is a village that has local potential, with local residentspredominantly working as fishermen, where the fishermen only make use of it by selling raw fish harvests.The relatively cheap price does not provide significant benefits to their income, so innovation is needed toprocess it further. Seeing this kind of situation, it is necessary to hold training on processing tuna intoready-to-eat food such as fish floss in order to increase the selling value of tuna. Making fish floss does notrequire large costs and is easy for tuna farmers to apply. Meanwhile the selling value is relatively betterthan the selling value of raw fish. Problems in the field in this service activity were explored throughobservation and interview methods. After the problem was identified, preparations for training andoutreach were carried out, then training was carried out on making fish floss. This activity succeeded inproviding an understanding of the importance of increasing the added value of fish production through processing it into fish floss, providing skills in making fish floss. Further service activities can be directedat efforts to assist the community in obtaining P-IRT permits, assisting with sales via social media, andassisting the next production innovation process, including by trying various other flavor variants besidesthose tested in the current service activity.